The believing scientist : essays on science and religion - Barr, Stephen M., 1953- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2016)
Elegant writings by a cutting-edge research scientist defending traditional theological and philosophical positions. Both an accomplished theoretical physicist and a faithful Catholic, Stephen Barr in this book addresses a wide range of questions about the relationship between science and religion, providing a beautiful picture of how they can coexist in harmony. In his first essay, "Retelling the Story of Science," Barr challenges the widely held idea that there is an inherent conflict between science and religion. He goes on to analyze such topics as the quantum creation of universes from nothing, the multiverse, the Intelligent Design movement, and the implications of neuroscience for the reality of the soul. Including reviews of highly influential books by such figures as Edward O. Wilson, Richard Dawkins, Stephen Jay Gould, Francis S. Collins, Michael Behe, and Thomas Nagel, The Believing Scientisthelpfully engages pressing questions that often vex religious believers who wish to engage with the world of science. - from publisher.
Science versus religion? Retelling the story of science -- Evolution. Evolution without tears -- The devil's chaplain confounded -- Mismeasure of man -- The design of evolution -- Chance, by design -- Debating Darwin -- The end of intelligent design? -- Mind and soul. More than machines: physics and free will -- Does quantum mechanics make it easier to believe in God? -- Faith and quantum theory -- A mystery wrapped in an enigma -- Thomas Nagel on the human mind -- Matter over mid -- Theories of everything -- The big bang and creation. Modern physics, the beginning, and creation -- Physics, the nature of time, and theology -- Much ado about "nothing": Stephen Hawking and the self-creating universe -- Reductionism. Fearful symmetries -- The human genome in human context -- Science as a substitute for religion. The idol of science -- Prophet of pointlessness -- Finding God through science. The (scientific) case for God -- The form of speaking -- Mischievous myths about scientific revolutionaries. From myth to history and back -- Crackpots and the Einstein myth.
Includes bibliographical references.
Print version record.
Keywords: Religion and science; Religion and science; BODY, MIND & SPIRIT / Gaia & Earth Energies; RELIGION / Christianity / General; Electronic books